Pengaruh Kesadaran Wajib Pajak, Pemahaman Peraturan Perpajakan dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak (Studi Empiris Wajib Pajak Pribadi di Wilayah KPP Pratama Cikupa - Tangerang) - Adrian Hidayat; Georgius Listen; Tri Angreni Angreni (Komunitas Dosen Indonesia, 2022)
This study aims to determine how far product quality and price affect purchasing decisions at PT. Leo Fam Facilities. The research conducted is by distributing questionnaires, while the research method used is descriptive method. In conducting this research, the writer uses correlation coefficient analysis, multiple linear regression analysis and F test and t test. From the results of the analysis the authors obtain the following results. From the multiple linear analysis, the equation Y = 1.583 + 0.542 X1 + 0.510 X2 means that for every 1 point increase or decrease in price, the purchasing decision will increase and decrease by 0.542. On product quality, every 1 point increase or decrease, the purchase decision will increase or decrease by 0.510. From the correlation coefficient analysis, it is shown that the price correlation coefficient is 0.953, close to 1, and the product quality correlation coefficient is 0.948, close to 1, so the relationship is strong and has a positive relationship with purchasing decisions at PT. Leo Fam Facilities. From the results of the F test for model 1, the value is 716,380 and for model 2 is 573,529 where both values ??are greater than the F table of 1.96, thus Ho is rejected and Ha is accepted. In the t-test, the results are known, in the t-column it is known that the t-count for the price (X1) is 7.108 while the t-count column for product quality (X2) is 6, 382 by using the t normal distribution table and using the degree of freedom or (df) n - 2 = 75 – 2 = 73, the value of the t table distribution is 1.666. Because t count product quality and price > from table t which is 1.666, then Ho is rejected and Ha is accepted.